Fabrication of Simple and Ring-Type Piezo Actuators and Their Characterization. (4th January 2012) - Sahoo, B.; Panda, P. K.
Abstract : A piezo multilayered stack of height 10 mm is fabricated using 80 μ m thick PZT tapes prepared by tape-casting technique. About 120 layers of thin tapes are dried, screen-printed with Pt-electrode paste, stacked, laminated, and then isopressed to obtain a green multilayered stack. Cofiring of the stack is carried out at1250 ∘ C for 1 h with very slow heating rate (15 ∘ per 1 h). The sintered stack is poled at 2 kV per mm in hot (120 ∘ C) silicone oil bath for 45 minutes, and free displacement and block force were characterized. The actuator generates free displacement of 10 μ m (0.1% strain) and block force of 1427 N at 175 V. In a similar way, a ring-shaped multilayered PZT stack was fabricated; the displacement was measured to be 8 μ m. The ring-type actuator is mainly used for fluid flow control in space vehicles.